Analisis Skala Usaha, Pendapatan Usaha dan Pengalaman Usaha terhadap Penggunaan Informasi Akuntansi pada Pelaku UMKM di Kota Batam - Neni Marlina Br Purba; Khadijah Khadijah (LPPM Universitas Putera Batam, 2020)
This study aims to determine how the influence of business scale, business income and business experience on the use of accounting information for MSME actors in the city of Batam. This type of research is quantitative research and uses primary data in the form of a questionnaire distributed by google form. The population in this study were all MSME actors who registered their business at the Batam City Cooperative and UMKM office. The sampling technique used simple random sampling and used the Slovin formula in order to obtain a sample of 94 MSMEs. Data analysis techniques used instrument tests (validity and reliability), descriptive analysis, classical assumptions consisting of normality, heteroscedasticity and multicollinearity tests, multiple linear regression, partial test, simultaneous test and coefficient of determination test. Based on the results of data processing using the SPSS program, the following research results were obtained: Partially, business scale and business income have a positive and significant effect on the use of accounting information. Meanwhile, business experience partially does not have a significant effect on the use of accounting information. Simultaneously, business scale, business income and business experience have a significant effect on the use of accounting information for MSMEs in Batam. Based on the coefficient of determination, the Adjusted R Square figure is 0.428, indicating that business scale, business income and business experience have an effect of 42.8% and the rest is influenced by other variables outside of this study.